2022
DOI: 10.3389/fpsyg.2022.923795
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sustained Literacy Engagement on Cognition and Sentence Processing Among Older Adults

Abstract: Considerable evidence suggests that language processing depends on memory processes, which are vulnerable to declines with aging. Yet little is known about the effects of language processing in the form of sustained literacy engagement on memory and other aspects of cognition. In the current study, adults (60–79 years of age) were randomly assigned to an 8-week program of leisure reading (n = 38) or to an active puzzle control (n = 38). Relative to the control, the experimental group showed differential improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 164 publications
(201 reference statements)
0
6
0
Order By: Relevance
“…Higher levels of print exposure have been found to be associated with buffering of the effects of working memory on sentence wrap-up and sentence recall (Payne et al, 2012, 2014). A recent training study further demonstrated the potential of utilizing sustained literacy engagement as a means to offset age-related deterioration in cognitive functions (E. A. L. Stine-Morrow et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of print exposure have been found to be associated with buffering of the effects of working memory on sentence wrap-up and sentence recall (Payne et al, 2012, 2014). A recent training study further demonstrated the potential of utilizing sustained literacy engagement as a means to offset age-related deterioration in cognitive functions (E. A. L. Stine-Morrow et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of print exposure have been found to be associated with buffering of the effects of working memory on sentence wrap-up and sentence recall (Payne et al, 2012(Payne et al, , 2014. A recent training study further demonstrated the potential of utilizing sustained literacy engagement as a means to offset agerelated deterioration in cognitive functions (E. A. L. Stine-Morrow et al, 2022). In particular, compared to a puzzle activity group, participants who engaged in leisure fiction reading for at least 30 min daily over an 8-week period demonstrated significant enhancements in several cognitive functions, including working memory, processing speed, and conceptual integration.…”
Section: Life-long Habits Of Literacymentioning
confidence: 99%
“…Arikpo argues that interest is a feeling of preference and interest in something or activity without being told (Arikpo, 2015). Reading can be an activity that can affect a person's cognitive function (Stine-Morrow et al, 2022).…”
Section: Frequency (Often or Not)mentioning
confidence: 99%
“…Arikpo argues that interest is a feeling of preference and interest in something or activity without being told(Arikpo, 2015). Reading can be an activity that can affect a person's cognitive function(Stine-Morrow et al, 2022).Interest in reading is a positive attitude towards lesson activities and a sense of interest in reading books. Interest in reading is a solid and deep concern accompanied by a feeling of pleasure towards lesson activities so that it can direct a person to read on their own accord or encouragement from outside(Putri, 2021).…”
mentioning
confidence: 99%
“…On the other hand, older people tend to have greater exposure to written language, so that they acquire greater linguistic knowledge (Hartshorne & Germine, 2015) and more general world knowledge (Horn & Cattell, 1967), which might help to preserve efficient language processing strategies. Indeed, the maintenance of reading skills among older adults may well-depend on continued literacy experience (e.g., Payne et al, 2012; Stine-Morrow et al, 2022).…”
mentioning
confidence: 99%